Editorial: Recent Developments in Prospect Theory-based Travel Behaviour Research - Avineri, Erel; Chorus, Caspar G. (European Journal of Transport and Infrastructure Research, 2010)
Prospect theory, a descriptive approach of modelling individual choice making which has been applied in a range of contexts, has recently attracted the interest of transport academics and professionals and is seen by many as a promising framework for travel behaviour modelling. This special issue follows a seminar on prospect theory and its applications to transport held in Delft at October 2009. It features a selection of carefully reviewed papers that were presented at the seminar. This special issue aims to expose the reader to the recent developments in this field and to some particularly relevant theoretical discussions, potential applications and critical views of prospect theory and its potential applications in the study of travel behaviour.